Let's Talk It Over: Communication and Coordination in Teams - Jens Dietrichson; Jens Gudmundsson; Torsten Jochem (Lund University, School of Economics and Management, Department of Economics, 2018)
Collaboration in teams in which each member's output is critical to the overall success present organizations with difficult coordination problems. We develop a model and run simulations to analyze how costly communication affects team coordination and output efficiency. We show that absent any organizational routines to structure team communication the least efficient outcome is the most frequent organizational output. We then derive formal conditions and simulate efficiency gains for several communication routines that improve team coordination and organizational efficiency. Our model and simulation results match a broad range of findings from the experimental and organizational literature, help explain why collaborations involving several organizational units often fail, and suggest new tests for promising communication routines.
Keywords: C73; D02; D23; L22; L23; 330; Coordination; Communication; Teams; Routines; Authority